Toward well-organised ionic discotic liquid crystals via versatile supramolecular approach. Issue 9 (15th July 2018) - Mu, Bin; Chen, Keyang; Chen, Jian; Fang, Jianglin; Chen, Dongzhong
ABSTRACT: Various ordered structures of crystalline three-dimensional (3D) cubic, 2D columnar or 1D lamellar mesophases have been facilely achieved through host–guest interactions of electrically neutral host tris(18-crown-6)triphenylene and guest potassium sulfonates with alkyl tails of variant number and length. The convenient construction of functionalised ionic complexes and the flexibility of such a supramolecular approach offer a wide variety of possibilities to prepare various ordered functional soft materials, especially those in their 2D ordered columnar liquid crystalline mesophases may serve as promising electron and ion dual-channel transport organic electronic materials. Graphical Abstract: